Acute Otitis Media in Children: Etiopathogenesis, Symptoms, And Treatment (Texas Journal of Medical Science, 2024)
Acute otitis media, commonly known as an ear infection, is a prevalent and often painful condition that primarily affects children, especially those under the age of two. AOM involves inflammation of the middle ear, often caused by viral upper respiratory infections that spread through the Eustachian tube. Factors contributing to AOM include viral and bacterial infections, Eustachian tube dysfunction, anatomical variations in young children, and environmental factors like secondhand smoke exposure. Symptoms of AOM include ear pain, fever, irritability, pulling at the ears, fluid drainage, hearing loss, and loss of appetite